1997
DOI: 10.1073/pnas.94.16.8860
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of spectral tuning in the mouse green cone pigment

Abstract: Diversification of cone pigment spectral sensitivities during evolution is a prerequisite for the development of color vision. Previous studies have identified two naturally occurring mechanisms that produce variation among vertebrate pigments by red-shifting visual pigment absorbance: addition of hydroxyl groups to the putative chromophore binding pocket and binding of chloride to a putative extracellular loop. In this paper we describe the use of two blue-shifting mechanisms during the evolution of rodent lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
153
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(166 citation statements)
references
References 36 publications
13
153
0
Order By: Relevance
“…About 3% of the photoreceptors in the mouse retina are cones that resemble rods at the light-microscopic level (25). However, UV-and mid-wavelength-sensitive cones have spectral maxima at 355-359 nm and 508-511 nm, respectively (16,26,27), whereas the murine rod is maximally sensitive at 502-503 nm. Also, mammalian rods express only a single type of pigment, but at least some cones contain a pigment mixture (16,28).…”
Section: Discussionmentioning
confidence: 99%
“…About 3% of the photoreceptors in the mouse retina are cones that resemble rods at the light-microscopic level (25). However, UV-and mid-wavelength-sensitive cones have spectral maxima at 355-359 nm and 508-511 nm, respectively (16,26,27), whereas the murine rod is maximally sensitive at 502-503 nm. Also, mammalian rods express only a single type of pigment, but at least some cones contain a pigment mixture (16,28).…”
Section: Discussionmentioning
confidence: 99%
“…Several mutation analysis studies targeting positions 83 and 292 have been conducted. S292A in RH1 pigments in coelacanth or a replacement at the corresponding position in mammalian red and green pigments shifts the max values 8-28 nm toward red (32,50,51), although the reverse mutation in human pigment did not cause any change (52). It was also reported that D83N in bovine RH1 pigment shifts the max values 6 nm toward blue (53).…”
Section: Discussionmentioning
confidence: 89%
“…The identity of these sequences as orthologues of the LWS sequences in other vertebrate species was obtained by phylogenetic analysis where both form a clade with other LWS sequences (figure 2b). The l max values of LWS pigments across different mammalian species vary from 508 nm in the mouse, Mus musculus (Sun et al 1997), to approximately 565 nm in primates (Bowmaker et al 1991). Since the separate MWS and LWS classes of cone photoreceptors that have been identified by MSP in the retinae of both the honey possum and the fat-tailed dunnart show a similar range with the l max values at 505 and 557 nm for the honey possum, and at 509 and 535 nm for the fat-tailed dunnart, in vitro expression of the fat-tailed dunnart sequence was used to determine the l max of the encoded opsin.…”
Section: Resultsmentioning
confidence: 99%
“…The LWS pigment in the mouse, M. musculus, has a l max at 508 nm, which is similar to the l max values of the marsupial MWS pigments. This shortwave shift in the mouse pigment arises from a Ser rather than the more usual Ala residue at site 308 combined with the loss of chloride binding arising from a His197Tyr substitution in the chloride-binding site (Sun et al 1997). A genomic fragment that encompasses intron 4 of 776 bp and the flanking regions of exons 3 and 4, the latter including the coding region for His197, was PCR amplified from the fattailed dunnart genomic DNA using the primer pair LWSDC and LWSEK listed in table 1.…”
Section: (C) Mws Conesmentioning
confidence: 99%